Analysis of the Impact of Hybrid Working Policy on Employee Life Balance and Productivity - Pardomuan Pardosi; Siti Mujannah; Abdul Halik; Eko Winarni (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Hybrid working policies that combine work from home and office are increasingly being implemented in various companies. This change is influenced by the need to create a better work-life balance, as well as increase employee productivity. However, the impact of this policy on the life balance and productivity of employees still needs to be further researched. This study aims to analyze the impact of hybrid working policies on employee life balance and productivity, as well as to understand the factors that affect the success of these policies in various job sectors. This study uses a quantitative approach with a survey method involving employees from various sectors. Data was collected through questionnaires that measured employees' perceptions of life balance, productivity, and work experience in a hybrid policy. The results show that hybrid working policies improve life balance for most employees, with time and workplace flexibility being the main factors. Productivity also increased, although some employees reported challenges related to social isolation and decreased team collaboration. This impact varies depending on the job sector and the employee's position. This study concludes that hybrid working policies can provide significant benefits to employees' life balance and productivity, but their implementation must be adjusted to the characteristics of the sector and job position. Support from companies in facilitating the transition and good communication is needed to optimize this policy.